Factors Influencing Thai People’s Consumption of Organic Food Products Behavior - Khao-men Rungsriworawat, Kornjira; Ratpongporn, Tunpawee; Khaimook, Kanit (Journal of Humanities and Social Sciences, Rajapruk University, 2023)
The objectives of the research were to 1) investigate a model of the influence factors on knowledge about organic agriculture; psychological factors; social factors; and marketing mix factors on organic food consumption behaviors of Thai people, 2) investigate the model of linkage between the interaction effects of food safety awareness and the benefit perception of organic food products, influencing action between predictive variables affecting the consumption behaviors of organic food products of Thai people. This research was conducted using a quantitative research methodology. The data were collected from 1,100 customers around the country. The questionnaire was used as a tool to collect data. The descriptive statistical data consisted of percentages, confirmatory factor analysis and hierarchical regression. The research results showed that: 1) the structural model of all factors had a significant direct positive influence on consumer behaviors. The theoretical corroboration obtained from the literature review contained in the model was weighted for both direct and moderating influences. As for the interaction of moderating variables, the quantitative findings supported the conceptual model. 2) The statistical analysis results concluded that the variables according to the model can predict the consumers' consumption behaviors of organic food products by approximately 67.8 percent (R2=0.678).